Brachial artery perforator propeller flap reconstruction of post electrical burn defect axilla - Mahipathy, Surya Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Jayachandiran, Anand Prasath; Rajendran, Suresh (International Surgery Journal, 2021)
In the current scenario, propeller flaps are an attractive choice for single stage coverage of a large number of defects. They have a more reliable vascular pedicle than traditional flap and allow for greater freedom in design and wide mobilization and minimal donor-site morbidity. Harvesting of a propeller flap requires appropriate patient selection, preoperative planning, and meticulous dissection and these techniques greatly reduce the complication rates. Here, we present a case of a post burn raw area of the right axilla which was debrided and covered with a brachial artery perforator propeller flap.